Penerapan Multimedia Interaktif untuk Meningkatkan Motivasi dan Hasil Belajar IPA Materi Struktur Organ Tubuh Manusia dan Fungsinya - Dinar Arena Tiari; Nunuk Suryani; Suharno Suharno (Teknodika, 2016)
The purpose of this study was to: (1) Improving student motivation through the application of interactive multimedia in science for fourth grade at Brubuh 2 Elementary School; (2) Improving student learning outcomes through the application of interactive multimedia in science for fourth grade at Brubuh 2 Elementary School. This type of research is a classroom action research (PTK), the research subjects were 21 students of fourth grade at Brubuh 2 Elementary School. The research was conducted in two cycles, each cycle consisting of planning, action, observation, and reflection. Data collection techniques using the test (to measure student learning outcomes), the questionnaire (to measure student motivation), observation, interviews, and documentation. The validity of the data using triangulation techniques and data sources triangulation method. While the criteria for the success of this research if at least 80% of students had reached KKM (minimum completeness criteria) ≥ 70, and the percentage of learners' motivation towards science learning using interactive multimedia by 80%. The results showed that an increase in student learning outcomes, including an increase in the average grade of 60.38% pre-cycle into 72.41 % in the first cycle and 83.09% in the second cycle. The lowest value increased from pre cycles 50 to 60 in the first cycle and 65 in the second cycle. The highest value increase of pre cycles 76 to 90 in the first cycle and 100 in the second cycle. The number of students who reach KKM ≥ 70 also increased from 38.1% pre-cycle to 66.7% in the first cycle and 90.47% in the second cycle. The percentage of student motivation toward science learning by using interactive multimedia application amounted to 67.43% in the first cycle and increased to 84.23% in the second cycle. The second variable of this class action research has qualified research success criteria, that is motivation and completeness learning outcomes of students reached 80 %.